Daerah penangkapan ikan dari kapal huhate yang berpangkalan di Pelabuhan Perikanan Pantai Belang - Dedy Suprianto; Emil Reppie; Johnny Budiman (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2012)
Skipjack (Katsuwonus pelamis) is a leading economic activity in the fisheries sector of the North Sulawesi, commonly captured by pole and line fishing gear. To improve the fishing efficiency with the gear, it is indispensible to know the distribution of fishing ground and fishing seasons. This study was aimed describing the pole and line fishing gear and its fishing process, mapping the position of skipjack fishing ground landed in Belang Coastal Fishing Port, and predicting the skipjack fishing season, by using a descriptive method. Primary data gained by interviews and direct measurement techniques to know the position of fishing ground during fishing operation, supported by secondary data. Position data of skipjack catches landed at Belang port was plot on the base map as a thematic map. Fishing season was analyzed by comparing the average monthly catches and average total catches for the given year. Fishing ground of pole and line based in Belang Coastal Fishing Port for the year 2012 was situated in Moluccas Sea at geographical position 0000’5.48’’ N - 1016’2.12’’ N and 124004’5.48’’ E - 126022’5.38’’ E. Fishing season occurred in April for the first phase, then from July to September for the second phase, where the second phase is larger and longer.